KUALITAS PENTATAHAN RELIEF DI KOMPLEKS CANDI PRAMBANAN - Hari Lelono (Berkala Arkeologi, 1996)
Is there a relationship between the sculpting technique and the theme of the story? As is known in the Ciwa and Brahma Temples (the Ramayana story) tells the journey of a noble or king, so it requires complete accessories. On the other hand, in the Vishnu temple, Kresnayana's story tells of Kresna's "life journey" as a "human being" who socializes a lot with the lower community. In terms of the quality of the order, the sequence is as follows: First Ciwa Temple, Second Brahma Temple, and the third Vishnu Temple. Because it is a continuation of the Ramayana story, the Brahma Temple is one level better than that of Vishnu Temple.